2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037392
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of electronic stethoscopes for cardiac auscultation

Abstract: There are several electronic stethoscopes available on the market today, with a very high potential for healthcare namely telemedicine, assisted decision and education. However, there are no recent comparatives studies published about the recording quality of auscultation sounds. In this study we aim to: a) define a ranking, according to experts opinion of 6 of the most relevant electronic stethoscopes on the market today; b) verify if there are any relations between a stethoscope's performance and the type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…While stethoscope auscultation is a valuable and oftentimes first applied tool in primary health care, its digitization is a relatively recent development leading to applications including classification of mitral valve prolapse [23] and the detection of other abnormal heart sounds [24]. Currently available digital stethoscopes are designed close to the traditional implementation [25], with a few exceptions lately emerging [26]. To the best knowledge of the authors, no wearable digital stethoscope implementation was available until very recently.…”
Section: Clinical Background and State-of-the-artmentioning
confidence: 99%
“…While stethoscope auscultation is a valuable and oftentimes first applied tool in primary health care, its digitization is a relatively recent development leading to applications including classification of mitral valve prolapse [23] and the detection of other abnormal heart sounds [24]. Currently available digital stethoscopes are designed close to the traditional implementation [25], with a few exceptions lately emerging [26]. To the best knowledge of the authors, no wearable digital stethoscope implementation was available until very recently.…”
Section: Clinical Background and State-of-the-artmentioning
confidence: 99%
“…The design of CAD systems for heart sound signals analysis with good sensitivity and specificity for abnormal heart sounds poses some non-trivial challenges. The analysis starts from the acquisition and digitalization of the heart recordings into a digital phonocardiogram (PCG), which is usually performed with an electronic stethoscope [8]. The bandwidth necessary to convey clinically relevant information ranges from as low as 20 Hz to 650 Hz [9,10].…”
Section: (B) Automated Phonocardiogram Processing For Computer-aided Diagnosismentioning
confidence: 99%
“…However, their high cost which can range from several hundred to several thousand AUD make them less suitable for use in ED, where contamination and damage can easily occur [18]. A study by Pinto, et al [19] also concluded that whilst features may vary between leading market ES, their performance were similar, showing advanced features are not essential for effective use in triage assessment. A low cost specifically triage assessment design, is, therefore, more desirable than the implementation of costly electronic stethoscopes marketed towards specialist practitioners.…”
Section: Introductionmentioning
confidence: 99%